(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Aim & Objective: To see the spectrum of chest X-ray abnormalities in sputum positive T.B patients. Methodology: In this descriptive cross sectional study a total of 120 patients aged 16-80 years of either sex, with sputum positive smear were taken from the Pulmonary Tuberculosis department of Gulab Devi Chest Hospital, whose chest X-rays were interpreted to see the suspicion of PTB and related spectrum of abnormalities on chest X-rays. Results: Mean age of our patients was 40.7±16.8 years with male to female ratio of 1:1.4. Bilateral lung was involved in 62 (51.7%) patients and 58 (48.3%) patients have unilateral involvement of lung in chest X-rays. 68 (56.67%) patients had Infiltrative shadows. Cavitatory lesions were present in 49 (40.83%) cases and only 3 (2.5%) patients had non-cavitatory lesions on chest X-rays. Opacity or consolidation was seen in 41 (34.1%) cases while abnormalities in terms of pleural effusion or pneumothorax was seen in only 18 (15%) cases in CXR. Conclusion: Common abnormalities on Chest X-ray in sputum positive TB patients include infiltrative shadows following opacity/consolidation and pneumothorax/pleural effusion. Early Chest X-ray leads to early diagnosis of PTB. Not even a single normal CXR was obtained so we conclude that the probability of detecting AFB on sputum smear is greatly influenced by suspected CXR abnormalities.